Effect of the inclusion of raw meat in a cooked pâté of mechanically recovered rainbow trout meat - Jimenez Champi, Diana Carolina (2021)
The fishing industry generates large quantities of by-products, most of which are not used and are therefore discarded. The objective of the present research was the elaboration of a pâté-type sausage from mechanically recovered meat of rainbow trout (Oncorhynchus mykiss). The meat was obtained from trout skelons, which were passed through a grinder and sprayed with a mixture of α-tocopherol (0.02%) and ascorbic acid (0.05%). The formulation of the pate was as follows: mechanically recovered trout meat (74.4%), salt (1.3%), sodium tripolyphosphate (0.8%), starch (2%), soy protein isolate (2.4%), margarine (16.7%), soy lecithin (1.9%), onion powder (0.2%), garlic powder (0.2%) and pepper powder (0.1%). Three formulations were prepared: PCR1 (80% cooked meat and 20% raw meat), PCR2 (90% cooked meat and 10% raw meat) and PCR3 (100% cooked meat). For each formulation, the following were evaluated: texture profile, color and sensory evaluation, the latter with the participation of 30 untrained panelists using a 9-point hedonic scale, in which each formulation obtained an average of 6 ("I like it moderately"). The best formulation was PCR3, whose proximate composition was determined: 64% moisture, 16% fat, 12.5% protein, and 3.5% ash. The pâté of mechanically recovered trout meat proved to have a high nutritional value and a good level of sensory acceptance, demonstrating that it is a good alternative for the use of trout fillet by-products.